Growth hormone 1 and insulin 2 gene polymorphism in Egyptian chickens - EL-KADER, HEBA AMABD; ISHAFEY, HEBA; EMEL-KOMY, EMEL-KOMY; SALAM, SALLY; FMAHROUS, KARIMA (The Indian Journal of Animal Sciences, 2019)
The genetic polymorphism of two genes related to growth production in four chicken breeds (Dokki 4, Inshas, El-Salam and Mandarah) were studied. PCR-RFLP and single nucleotide polymorphism (SNPs) analysis were studied in the two genes namely GH1 and insulin 2. Blood samples were collected randomly from 84 chickens, DNA was extracted and genotypes for two genes were detected using PCR-RFLP analysis. The locus GH1 (467 bp) showed two genotypes (GG, AG) in four chicken breeds due to the presence of two Msp1 restriction sites (C^CGG) in intron1. The sequence analysis revealed two substitutions (C/T) in Dokki 4 and Inshas breeds, G/A substitution in Dokki 4 and Mandarah breeds and insertion of T nucleotide in four chicken breeds. In insulin 2 gene (371 bp), two genotypes (TT, TC) were recorded in four chicken breeds due to presence of one restriction site in intron1. The nucleotide substitutions (A/G) and (T/C) were observed in all Egyptian chicken breeds except Inshas breed and A/ T transversion was observed in all breeds. The sequences of detected SNPs were submitted to GenBank database with the accession numbers MG906782–MG906789 in GH1 gene and the accession numbers MG906790–MG906791 in insulin 2 gene. In conclusion, the presence of certain polymorphisms could increase the phenotypic variety and will be supportive in selection and breeding programs.